Telling and selling: a consideration of the pedagogical work done by nationally endorsed corporate-sponsored educational resources. Issue 1 (2nd January 2016) - Robinson, Daniel B.; Gleddie, Doug; Schaefer, Lee
ABSTRACT: In recent times, not-for-profit organisations have been partnering with for-profit corporations to create educational resources. This has been especially true in physical and health education, particularly within Canada. For example, Physical and Health Education Canada has recently endorsed a number of corporate-sponsored educational resources related to health and wellness. Given this observation, we have recognised a need to theorise about how such resources – when considered as pedagogical texts – do pedagogical work. Ascribing to the belief that such resources are shaped by corporations' biased, value-laden, and ideological views, we suggest that the desired knowledge(s) of corporations are necessarily present, if not influential or foundational, when such resources are conceived, produced, and distributed. By turning our attention to this belief and suggestion, we provide a necessary critique of these resources and the pedagogical work they achieve. We have done this by attending to the scholarship of Bernstein [2000. Pedagogy, symbolic control and identity: Theory, research, critique. Lanham, MA: Rowman and Littlefield], with some additional attention to curriculum theorising done by Tinning [2010. Pedagogy and human movement: Theory, practice, research. New York, NY: Routledge]. We are hopeful that our analysis promotes discussion, debate, and potential (re) action in response to this current practice.